EKSPLORASI ETNOMATEMATIKA PADA BANGUNAN PURA DI DESA RAMA AGUNG KABUPATEN BENGKULU UTARA - Riska Setianingrum; Rahmat Jumri; Masri Masri (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The ethnomathematics combines mathematics with the culture and traditions of society. The Culture is all values, thoughts, and symbols that influence the behavior, attitudes, and habits of a person and society, while mathematics is the knowledge that society uses to solve problems in everyday life. This study aimed to explore ethnomathematics in the architecture of Rama Agung Village Temple building, North Bengkulu Regency. This study is a qualitative descriptive by using an ethnographic approach method. The data collection technique of this study uses observation, interviews and documentation. The results of the study show that the form and architecture of the Rama Agung Village Temple Regency Temple buildings in North Bengkulu Regency have ethnomathematics realted to mathematical concepts including space and flat shapes. The concepts contained in the temple buildings can be used to introduce the concept of geometry though local culture.